The gender peculiarities of psychological training of managers of educational institutions - Кот, Г.М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2012)
The article is devoted to the research of structural components and personal determination of the students’ psychological training in order to develop psychological technologies for creation and development of general and special psychological skills, vocationally significant constituents of the professional and individual development of students.